LEARNING INDEPENDENCE OF BIOLOGICAL EDUCATION STUDENTS IN CALCULUS COURSE ONLINE REVIEWED BY GENDER - R. H. Yanti Silitonga (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
This research was conducted to determine the independence of student learning in calculus courses conducted online based on gender. This type of research is descriptive quantitative. The subjects in this study were 34 biology education students. There are 4 male students and 30 female students. Methods of data collection using a scale of learning independence. The results showed that there were significant differences in the learning independence of male and female students. Female students outperform male students for all indicators of independent learning. The percentage of the average score of male students 'learning independence was 59.37, while the percentage of the average score of female students' learning independence reached 66.54. Keywords :